Perlindungan Hukum Terhadap Eksploitasi Tubuh Sales Promotion Girl; Studi Komparasi Hukum Islam dan Hukum Positif - Tanjung, Abdul Jalil; Marilang (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
The topic of discussion in this journal is the legal protection against exploitation of the sales promotion girl (SPG) body which is discussed in the legal order in Indonesia. Sales Promotion Girl (SPG) then received various forms of physical and non-physical exploitation which referred to Law no. 13 Regarding Manpower and the Criminal Code. Sales Promotion Girl (SPG) is a profession for women who are active in marketing or promoting a product by the company. Sales Promotion Girl (SPG) in carrying out their work not infrequently workers have to go to the field in the midst of a crowd to sell or promote products from companies where most of the consumers are men. The Sales Promotion Girl (SPG) body seems to play an important role in marketing the company's products because attractive appearance is the main criterion in this job, workers often experience other forms of exploitation and abuse at work. the author takes the understanding that there is exploitation of women's bodies as Sales Promotion Girl (SPG) and how the law provides legal protection against forms of exploitation experienced by Sales Promotion Girl (SPG) workers and how the analysis of Islamic law and positive law on the exploitation of women's bodies as sales promotion Girls (SPG).